Robust hydrophobic surfaces from suspension HVOF thermal sprayed rare-earth oxide ceramics coatings - Bai, Mingwen; Kazi, H.; Zhang, X.; Liu, J.; Hussain, Tanvir (Nature Publishing Group, 2018)
This study has presented an efficient coating method, namely suspension high velocity oxy-fuel (SHVOF) thermal spraying, to produce large super-hydrophobic ceramic surfaces with a unique micro- and nano-scale hierarchical structures to mimic natural super-hydrophobic surfaces. CeO2 was selected as coatings material, one of a group of rare-earth oxide (REO) ceramics that have recently been found to exhibit intrinsic hydrophobicity, even after exposure to high temperatures and abrasive wear. Robust hydrophobic REO ceramic surfaces were obtained from the deposition of thin CeO2 coatings (3–5 μm) using an aqueous suspension with a solid concentration of 30 wt.% sub-micron CeO2 particles (50–200 nm) on a selection of metallic substrates. It was found that the coatings’ hydrophobicity, microstructure, surface morphology, and deposition efficiency were all determined by the metallic substrates underneath. More importantly, it was demonstrated that the near super-hydrophobicity of SHVOF sprayed CeO2 coatings was achieved not only by the intrinsic hydrophobicity of REO but also their unique hierarchically structure. In addition, the coatings’ surface hydrophobicity was sensitive to the O/Ce ratio, which could explain the ‘delayed’ hydrophobicity of REO coatings.